Geography and its teaching process in basic education: required reflections - Almeida, Ricardo Santos de; Melo, Maria Aparecida Vieira de (Revista Ensino de Geografia (Recife), 2021)
This article aims to support reflections on the process of teacher training in Geography in Basic Education, problematizing the repercussions of the theoretical-methodological assumptions of Critical Geography that must be permeated in didactic-pedagogical practices, namely: the analysis of everyday life, of problems economic, social, cultural and, above all, the environment. These formative and operational contributions to the teaching of Geography are inserted in the structuring relationships that permeate academic formation and must be provided in practice in school spaces. Therefore, the methodology consisted of associating the understanding of how the operationalization of theoretical-methodological assumptions can be valued in the practice of the teacher-researcher in his didactic-pedagogical action based on the theoretical contributions of Mello (2000), Pimenta (2002), Pontuschka et al (2007), Schon (2000), Simielli (2007) Silva et al (2016), Tardif (2012) among others, contributing to rethinking the objective and subjective dimensions existing throughout the formative process and its practice in Geography.